2012
DOI: 10.1155/2012/564612
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Human-Induced Pluripotent Stem Cells by a Nonintegrating RNA Sendai Virus Vector in Feeder-Free or Xeno-Free Conditions

Abstract: The generation of induced pluripotent stem cells (iPSCs) from somatic cells has enabled the possibility of providing unprecedented access to patient-specific iPSC cells for drug screening, disease modeling, and cell therapy applications. However, a major obstacle to the use of iPSC for therapeutic applications is the potential of genomic modifications caused by insertion of viral transgenes in the cellular genome. A second concern is that reprogramming often requires the use of animal feeder layers and reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 29 publications
1
49
0
Order By: Relevance
“…SeV reprogramming of human PGCs was performed, as previously described [45,46], using a Cytotune reprogramming kit (Lifetech) according to the manufacturer's instructions. The day before transduction, *100,000 PGCs were plated in PGCIII medium in a 6-well plate, and on day 0, the cells were incubated with virus at a MOI of 3 for 24 h. Afterward, the media was changed, and the cells fed every other day.…”
Section: Sev Reprogrammingmentioning
confidence: 99%
“…SeV reprogramming of human PGCs was performed, as previously described [45,46], using a Cytotune reprogramming kit (Lifetech) according to the manufacturer's instructions. The day before transduction, *100,000 PGCs were plated in PGCIII medium in a 6-well plate, and on day 0, the cells were incubated with virus at a MOI of 3 for 24 h. Afterward, the media was changed, and the cells fed every other day.…”
Section: Sev Reprogrammingmentioning
confidence: 99%
“…Sun et al (21) generated human iPSCs from adult human adipose stem cells, and Beltrão-Braga et al (29) subsequently derived iPSCs from human immature dental pulp stem cells without feeder cells. Recently, Macarthur et al (30) suggested that human neonatal fibroblast cells were able to be reprogrammed by transcription factors using a xeno-free culture system.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Therefore the risks of tumorigenesis can be avoided at the step of reprogramming factor induction [20][21][22][23][24] . Additionally, the feeder-free conditions, which use a combination of defined culture medium and matrigel instead of a feeder layer, make it possible to minimize the potential risks of exposure to unknown exogenous factors.…”
Section: Discussionmentioning
confidence: 99%